Legal aspects of privately financed infrastructure projects (PFIPs) in China: the case for international standards - Liang, Shuang (University of Leeds, 2013)
This thesis discusses the reform and improvement of Chinese legislation on Privately Financed Infrastructure Projects (PFIPs), to develop the PFIP model in China, under the protection of Chinese laws, so that its implementation in China may reach international standards. Existing Chinese laws are found to be insufficient in reducing risks to PFIPs because of certain shortcomings. Therefore, it is necessary to reform and improve Chinese legislation on PFIPs, to prevent their failure. The Legislative Guide and Model Provisions drafted by UNCITRAL are treated as the international standards to guide Chinese legislation reform on PFIPs. Other countries’ laws on PFIPs provide supplementary reference. This thesis addresses its aim in four steps: First, the current Chinese legislative and institutional framework on PFIPs is reviewed, with discussion on establishing a more appropriate legislative and institutional framework, to facilitate the development of PFIPs in China through the principles of transparency, fairness, long-term sustainability and the elimination of undesirable restrictions. Second, Chinese laws on the concessioner selection procedure in PFIPs are reviewed, with discussion on possible improvements to the laws to achieve international standards of fairness and transparency. Third, current Chinese laws and policies which affect the various contracts involved in PFIPs are reviewed, with discussion on these may be improved to achieve international standards. Fourth, the PFIP dispute settlements that may be used in China are reviewed, with discussion on the necessity to remove certain undesirable restrictions in relevant Chinese laws. Following the rapid rise in the practical use of PFIPs in China, this thesis offers a strong theoretical basis for suggesting a reform of Chinese legislation on PFIPs. It also provides a general basis for any national reform of laws on PFIPs in any other countries.

Law harmonization and local specificities – a case study: OHADA and the law of contracts - Fontaine, Marcel (Uniform Law Review, 2013)
Unifying or harmonizing the laws of different countries means replacing, to respective degrees, the existing national laws with common rules.1 The merits of law unification or harmonization may seem to be obvious. They have been repeatedly described. Law diversity is an obstacle to trade between countries. Engaging in a commercial operation with a partner of another legal system immediately raises the question of which law will govern the relationship, with the consequence that, for one of the parties, the contract will be subject to unfamiliar rules (perhaps even for both parties if the law of a third party is determined to be applicable).

The Problem of the Taxation of Internet Transactions - Asada, Dominic (Current Jos Law Journal, 2013)
Accepted: 2017-08-16T12:06:13Z